Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/tesq.308
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Development: A Vygotskian Approach to Transforming Second Language Learner Abilities

Abstract: The authors point to systemic‐theoretical instruction (STI), which underscores the importance of abstract conceptual knowledge in schooling, and dynamic assessment (DA), in which mediators and learners function cooperatively, as examples of the theory–practice relation envisioned by Vygotsky (). This article proposes an interactional framework to bridge STI and DA. Mediated development (MD) emphasizes mediator–learner dialogic interaction in which the aim is not to assess emerging capabilities but rather to gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 20 publications
(27 reference statements)
2
40
0
4
Order By: Relevance
“…As discussed in previous sections, education practitioners have investigated the sociocultural framework for its potential to enhance teaching and learning practices from various perspectives (Lee, 2015;Poehner & Infante, 2016;Razak, Saeed, & Ahmad, 2013;Samana, 2013;Shaban, 2016a;Turk, 2008. Beyond classroom practices, the approach has been even used as a tool in teacher professional development (Shaban, 2016b;Shaban, Khatib, & Ebadi, 2010).…”
Section: The Implications Of the Vsa On Enhancing Interaction In Efl mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in previous sections, education practitioners have investigated the sociocultural framework for its potential to enhance teaching and learning practices from various perspectives (Lee, 2015;Poehner & Infante, 2016;Razak, Saeed, & Ahmad, 2013;Samana, 2013;Shaban, 2016a;Turk, 2008. Beyond classroom practices, the approach has been even used as a tool in teacher professional development (Shaban, 2016b;Shaban, Khatib, & Ebadi, 2010).…”
Section: The Implications Of the Vsa On Enhancing Interaction In Efl mentioning
confidence: 99%
“…Research outlets in educational psychology have indicated the importance and contribution of the Vygotskian framework to successful teaching and learning in general and in some fields such as sciences and teacher education (Belland, 2017;Haider &Yasmin, 2015;Harland, 2003;Kozulin, 2003;Lindblom, & Ziemke, 2002;Lourenço, 2012;Mahn, 2012;Shaban, 2016b). English language teaching professionals have also explored the contribution of the sociocultural approaches to teaching English as a second or a foreign language from various perspectives in different settings (Lee, 2015;Poehner & Infante, 2016;Rezaee & Azizi, 2012;Samana, 2013;Shaban, 2016a;Turk, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In mediated-learning experience, Feuerstein explains that visualizations, written explanation, models and examples are provided by mediators to stimulate the students to perform tasks (Poehner & Infante, 2017). These put in mind, a mediation which is selected by the teacher in the classroom can be in various types and categories depending on several considerations, such as students' abilities, learning objectives, and targeted tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In mediated-learning experience, the cognitive and affective domains are inseparable in learning processes; as a result, Feuerstein (2003) cited by Poehner and Infante (2017) states that affective elements, such as feeling of competence and belief of positive behavior, might have implications on the students' orientation and performance. Therefore, in presenting a task, the teacher, as a mediator and a mediation herself, should select appropriate mediation that requires some criteria.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions between learner and MKO, result in the development of a higher thinking capacity in the learner (Lantolf and Poehner, 2004). DA focuses specifically on these interactions between a learner and MKO and the role they play in the development of a learner's higher thinking capacity (Infante and Poehner, 2016).…”
Section: Introductionmentioning
confidence: 99%